LOCAL ETHNIC MALAY COMMUNITY KNOWLEDGE IN TRADITIONAL MEDICINE UTILIZATION AND ITS CONSERVATION STRATEGY IN EAST BELITUNG REGENCY, INDONESIA - Henri Henri; Erika Erpandi (Media Konservasi, 2021)
Belitung Malay is the largest ethnic group in the East Belitung Regency which is rich in biodiversity. In daily life, the people of East Belitung utilize biological resources for various necessities of life, including the utilization for health maintenance and treatment. However, along with the changing times and technological developments in the health sector, there are some changes in society in the use of biodiversity as traditional medicine. This study aims to examine the knowledge and perceptions of the Belitung Malay ethnic community on the use of traditional medicines. The method used in this study is a semi-structured interview with ethnographic techniques. Informants were selected using purposive sampling, in which they were considered to have a lot of knowledge about traditional medicine and its processing, such as traditional leaders, tribal chiefs, village heads, herbalists, and massage workers. The data were analyzed using descriptive analysis. The results of the interview show that people still use traditional medicine a lot. Traditional medicine is sourced from plant and animal raw materials. Community trust in traditional medicines is still quite high as indicated in the use of medicinal plants based on use values ​​reaching 0.64 and animal-sourced traditional medicines of 92.59. Even though the use-value is high for the Malay ethnic community, it seems that the existence of traditional medicinal materials has become increasingly difficult and scarce to obtain. In this case, to obtain these medicinal ingredients, people must go far into the forest. Key words: East Belitung, knowledge, medicinal animals, medicinal plants, traditional healers